Use of Rapid-Scan EPR to Improve Detection Sensitivity for Spin-Trapped Radicals - Mitchell, Deborah G. (The Biophysical Society, 2013)
The short lifetime of superoxide and the low rates of formation expected in vivo make detection by standard continuous wave (CW) electron paramagnetic resonance (EPR) challenging. The new rapid-scan EPR method offers improved sensitivity for these types of samples. In rapid-scan EPR, the magnetic field is scanned through resonance in a time that is short relative to electron spin relaxation times, and data are processed to obtain the absorption spectrum. To validate the application of rapid-scan EPR to spin trapping, superoxide was generated by the reaction of xanthine oxidase and hypoxanthine with rates of 0.1–6.0 μM/min and trapped with 5-tert-butoxycarbonyl-5-methyl-1-pyrroline-N-oxide (BMPO). Spin trapping with BMPO to form the BMPO-OOH adduct converts the very short-lived superoxide radical into a more stable spin adduct. There is good agreement between the hyperfine splitting parameters obtained for BMPO-OOH by CW and rapid-scan EPR. For the same signal acquisition time, the signal/noise ratio is >40 times higher for rapid-scan than for CW EPR. Rapid-scan EPR can detect superoxide produced by Enterococcus faecalis at rates that are too low for detection by CW EPR.